Geneza i rozwój subkultury hipisów w Stanach Zjednoczonych (wybrane konteksty) - Mrozek, Justyna (Studia Edukacyjne, 2017)
The aim of this article is to present the socio-cultural context of the development of the hippie subculture. The author definesthe term ‘subculture’, describes the ideology and the lifestyle of hippies and presents a typology of its members. The text shows that the hippie movement was the fruit of its time but was also related to the social phenomena from the past and continues to be an inspiration for the present.